Assistance in Making Interactive Learning Using Online Media for Teachers of SDN 24 Pinggir: Pendampingan Pembuatan Pembelajaran Interaktif Dengan Pemanfaatan Media Online Bagi Guru SDN 24 Pinggir - Desi Yasri; Arya Engla Harda; Yolnasdi Yolnasdi; Ermawati Ermawati; Machdalena Machdalena (Universitas Lancang Kuning, 2023)
Sekolah Dasar Negeri (SDN) 24 Pinggir is a mentoring partner who has limitations in meeting the demands of learning during Covid-19 pandemic and in digital era, so it has the potential to have degradation in education. The educators of SDN 24 Pinggir need assistance in opening their horizons and knowledge in utilizing the right media in making teaching materials, even evaluating with learning methods and models that are in accordance with the needs of their students. The platforms chosen to be used as mentoring materials are wordwall, wizer and liveworksheet. The platform was chosen with the consideration that it is easy to access, simple and easy to understand, has features that can accommodate the needs of educators and there are free of charge options. Training activities begin with observations in the form of questions and answers with teachers and school principal which are then continued with training. Furthermore, participants did hands-on practice, and were given feedback through post-training evaluations. the initial survey, the average teacher was hesitant (46.30%) in making and distributing learning material using the platform. However, there was an increase in knowledge of 98.15% (Knowing in theory and practice) after the training was given.